Comparison of two standard power networks for generation and load patterns in power system - Bostani, Ali (2019)
Network structure and active power generation pattern are effective factors on static loadability limit and buses and voltage stability. This paper has been considered IEEE 14-bus and 34-bus test network in order to create generation and load patterns. Creating generation and load patterns in these two test networks like almost uniform distribution of generation, generation dispersion, the allocate value from the sharing of centralized generation to distributed generations (DGs) and change generation values on the buses, especially putting generation on buses of weak network is investigated. The conducted analyzes on the obtained results from the desired generation patterns, the authors have realized that the generation uniform distribution between buses or change of generations centralized location or allocate percent from generations centralized sharing to distributed generations and putting these generations on load bus, in the event that with accurate and comprehensive investigation is associated improved voltage stability and loadability limit. By analyzing the different modes and review the results of similar patterns in these two systems, the different generation and load patterns effect mechanism of distributed generation units over the behavior of the system in terms loadability limit and voltage stability is achieved.